2005
DOI: 10.1007/s10681-005-4629-x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a genetic linkage map and QTL analysis of fiber-related traits in upland cotton (Gossypium hirsutum L.)

Abstract: A genetic linkage map with 70 loci (55 SSR, 12 AFLP and 3 morphological loci) was constructed using 117 F 2 plants obtained from a cross between two upland cotton cultivars Yumian 1 and T586, which have relatively high levels of DNA marker polymorphism and differ remarkably in fiber-related traits. The linkage map comprised of 20 linkage groups, covering 525 cM with an average distance of 7.5 cM between two markers, or approximately 11.8% of the recombination length of the cotton genome. The present genetic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 26 publications
(31 reference statements)
7
89
1
3
Order By: Relevance
“…Here we found many common characteristics of QTLs related to fiber quality traits as described in the previous reports involving interspecific maps [3,10,23,[33][34][35][36][37][38] and intraspecific maps [12,15,26,30,[39][40][41][42][43][44][45][46], although few common markers were used in the present research and the previous studies, and the maps covered different region parts of cotton genome, making it difficult to compare the common QTLs, some QTLs were detected and mapped on the same chromosomes and affect common traits. These include seven QTLs for fiber length located in the same chromosomal regions as reported earlier [10,26,34,41,42], two QTLs for fiber uniformity ratio located in the same chromosomal regions [43,46], two QTLs for fiber micronaire [10,43,44], three QTLs for fiber elongation [30,36,42,43,46,47], and 4 QTLs for fiber strength [26,34,36,43,44,46,47].…”
Section: Qtls For Cotton Fiber Quality Traitssupporting
confidence: 71%
See 1 more Smart Citation
“…Here we found many common characteristics of QTLs related to fiber quality traits as described in the previous reports involving interspecific maps [3,10,23,[33][34][35][36][37][38] and intraspecific maps [12,15,26,30,[39][40][41][42][43][44][45][46], although few common markers were used in the present research and the previous studies, and the maps covered different region parts of cotton genome, making it difficult to compare the common QTLs, some QTLs were detected and mapped on the same chromosomes and affect common traits. These include seven QTLs for fiber length located in the same chromosomal regions as reported earlier [10,26,34,41,42], two QTLs for fiber uniformity ratio located in the same chromosomal regions [43,46], two QTLs for fiber micronaire [10,43,44], three QTLs for fiber elongation [30,36,42,43,46,47], and 4 QTLs for fiber strength [26,34,36,43,44,46,47].…”
Section: Qtls For Cotton Fiber Quality Traitssupporting
confidence: 71%
“…These include seven QTLs for fiber length located in the same chromosomal regions as reported earlier [10,26,34,41,42], two QTLs for fiber uniformity ratio located in the same chromosomal regions [43,46], two QTLs for fiber micronaire [10,43,44], three QTLs for fiber elongation [30,36,42,43,46,47], and 4 QTLs for fiber strength [26,34,36,43,44,46,47]. For example, the chromosome regions where QTLs were detected for fiber length in our research matched those in an interspecific map developed from an F 2 population [10]; the QTLs may be common QTLs for fiber quality traits.…”
Section: Qtls For Cotton Fiber Quality Traitsmentioning
confidence: 65%
“…SSR molecular markers could also prove to be useful in the understanding of the molecular base of fiber growth, while they could be used in parallel in various breeding programs and mainly in programs that are aimed at improving the quality of cotton fiber as well as increasing yield. Recent studies have found that the molecular markers that show a correlation with the qualitative characteristics of fiber are located almost in all chromosomes of cotton (Guo et al, 2003;Park et al, 2005;Zhang et al, 2005;Abdurakhmonov et al, 2007;Kantartzi and Stewart, 2008). Molecular markers for lint percentage have been found on chromosomes 5, 9, 10, 12, 16, 18, 23, and 26, for micronaire on chromosomes 3, 9 and 16, for fiber strength on chromosomes 12, 15, 17, and 18, and for fiber length on chromosomes 2, 18 and 26.…”
Section: Resultsmentioning
confidence: 99%
“…To 1 These authors contributed equally to this work. 2 date, several genetic maps of cotton genomes have been constructed using diverse DNA molecular markers and mapping populations (Ulloa and Meredith 2000;Ulloa et al 2002;Zhang et al 2002;Lacape et al 2003;Mei et al 2004;Rong et al 2004;Zhang et al 2005;Frelichowski et al 2006). The most saturated tetraploid cotton map is from Rong et al (2004), which is composed of 2584 loci at 1.72-cM intervals in 26 linkage groups.…”
mentioning
confidence: 99%